Optimum Use of Acute Treatments for Hereditary Angioedema: Evidence-Based Expert Consensus - Longhurst, Hilary (Frontiers in Medicine, 2018)
Acute treatment of hereditary angioedema due to C1 inhibitor deficiency has become widely available in the last ten years and has greatly improved patients’ quality of life. Two plasma-derived C1 inhibitors (Berinert and Cinryze), a recombinant C1 inhibitor (Ruconest/Conestat alpha), a kallikrein inhibitor (Ecallantide) and a bradykinin B2 receptor inhibitor (Icatibant) are all effective. Durably good response is maintained over repeated treatments and several years. All currently available prophylactic agents are associated with breakthrough attacks, therefore an acute treatment plan is essential for every patient. Experience has shown that higher doses of C1 inhibitor than previously recommended may be desirable, although only recombinant C1 inhibitor has been subject to full dose-response evaluation. Treatment of early symptoms of an attack, with any licensed therapy, result in milder symptoms, more rapid resolution and shorter duration of action, compared with later treatment. All therapies have been shown to be well-tolerated, with low risk of serious adverse events. Plasma-derived C1 inhibitors have a reassuring safety record regarding lack of transmission of virus or other infection. Thrombosis has been reported in association with plasma-derived C1 inhibitor in some case series. Ruconest was associated with anaphylaxis in a single rabbit-allergic volunteer, but no further anaphylaxis has been reported in those not allergic to rabbits despite, in a few cases, prior IgE-sensitisation to rabbit or milk protein. Icatibant is associated with high incidence of local reactions but not with systemic effects. Ecallantide may cause anaphylactoid reactions and is given under supervision. For children and pregnant women, plasma-derived C1 inhibitor has the best evidence of safety and currently remains first line treatment.